(untitled) (Global Journal of Human-Social Science, 2022)
This paper investigates in the light of Catharine MacKinnon s feminist idea the culture of domination and submission of women present in patriarchal society Thus the author highlights in her works the role of pornographic media in the representation of the female figure as na object that is assume roles linked to sexuality aiming at the satisfaction of male desires Therefore it is seen that pornography is built as na instrument responsible for the naturalisation of the discriminatory perspective towards women in the various spheres os society Assuming that the obstacles to the effectiveness of gender equality are clear Moreover especially in the book Only words the issue of the right and regulation of pornography is presented as an important aspect of her study From this perspective MacKinnon is opposed to the understanding that pornography and its scenes would only be recognized as a speech responsible for generating defamation Therefore contrary to what is declared by the Law it seeks to demonstrate that pornography constitutes acts of discrimination since they imply real actions of violence which generate segregation Thus it explains that the justice can t assume a neutral position in order to ensure means for women to be recognised as subjects of rights in their own history